HUNIAN VERTIKAL MONODUALISME (INDIVIDUALISME-KOLEKTIVISME) - Hidayatul Reza; Franky Liauw (Jurusan Arsitektur dan Perencanaan, 2021)
The conflict between the two social understandings between individualism and collectivism does not need to be clashed, but instead it needs to be managed according to values, morals and ethics. So that it can become a social force for social life. In this issue, architects can play a role in cultivating a 'space' that is fit to the problem of individualism-collectivism. The research method used is a comparative and synergistic method. Literature in the form of journals and books on the phenomenon of individualism-collectivism is used as a reference and comparison. To be able to change a person's attitude, it is necessary to have an environmental role that creates events and events that occur repeatedly and continuously, gradually being absorbed into the individual and influencing the formation of an attitude. In order for this approach to be applied easily, this approach must be applied to basic human needs. In basic human needs there is a hierarchy of the most basic, namely physiological needs, the most basic needs to be fulfilled because they include things that are vital for survival, namely, clothing, food, and shelter. So in order to answer this issue, the vertical housing function is fixed. In addition, vertical housing is considered important because it responds to limited land and the increasing human population. Vertical housing with a collaborative space in grouped dwelling unit concept, because offers many possibilities, from people who live together sharing physical space to communities that share values, interests and philosophies of life. Grouping system is also be an important value and in community prefer to live in small community amount 4-10 members with various background. Consisted by good quality personal space and supporting facilities to develop self-potential as self-actualization. Keywords: collaborative; collectivism; individualism; monodualism; self actualization Abstrak Konflik dua paham sosial antara individualisme dengan kolektivisme tidak perlu dibenturkan, tetapi justru perlu dikelola menurut nilai-nilai, moral, dan etika, sehingga dapat menjadi kekuatan sosial bagi kehidupan bermasyarakat. Dalam isu ini, arsitek dapat berperan dalam mengolah ‘ruang’ yang fit terhadap permasalahan individualisme-kolektivisme. Metode penelitian yang digunakan adalah metode komparatif dan sinergis. Literatur berupa jurnal dan buku tentang fenomena individualisme-kolektivisme, dijadikan sebagai acuan dan pembanding. Untuk dapat mengubah sikap seseorang diperlukan peran lingkungan untuk menciptakan kejadian-kejadian dan peristiwa-peristiwa yang terjadi berulang-ulang dan terus-menerus, lama-kelamaan secara bertahap diserap kedalam diri individu dan memengaruhi terbentuknya suatu sikap. Agar pendekatan ini dapat diterapkan dengan mudah maka pendekatan ini harus diterapkan pada kebutuhan dasar manusia. Pada kebutuhan dasar manusia terdapat hierarki yang paling dasar yaitu kebutuhan fisiologis (physiological needs), kebutuhan yang paling dasar untuk dipenuhi karena meliputi hal-hal yang vital bagi kelangsungan hidup yaitu, sandang, pangan, dan papan. Sehingga untuk menjawab isu ini, ditetapkan fungsi hunian vertikal. Selain itu, hunian vertikal dinilai penting karena untuk mejawab keterbatasan lahan dan semakin tingginya populasi manusia. Hunian vertikal dengan mengusung konsep ruang kolaboratif pada setiap unit hunian yang dikelompokkan, karena menawarkan banyak kemungkinan, mulai dari orang-orang yang tinggal bersama dengan berbagi ruang fisik hingga komunitas yang juga berbagi nilai, minat, dan filosofi hidup. Sistem pengelompokan penghuni juga menjadi nilai penting dan dalam komunitas lebih menyukai jumlah yang sedikit 4-10 orang dengan latar belakang yang berbeda. Ditunjang dengan kualitas ruang pribadi yang baik dan fasilitas penunjang yang dapat mengembangkan potensi sebagai bentuk aktualisai diri.